Improving Nursing Work Services through Development Model of Quality of Nursing Work Life - Tri Ismu Pujiyanto; Suprihati Suprihati; Nursalam Nursalam; Anastasia Ediyati (Universitas Airlangga, 2017)
Introduction: The performance of nurses in a hospital is influenced by the mental and emotional state of the nurse; the higher the workload, the greater the work stress of the nurse. It is a necessity to conduct research to explain a quality of nursing work life model based on the context of Indonesian nurses.Methods: The research process consisted of two stages: observational analytic and model trial. The first phase used cross-sectional design with cluster random sampling technique and obtained 102 samples. The second stage used a quasi-experiment design with pre-post test with control group design and obtained 33 samples. The data was analysed by Partial Least Squares and paired t-test analysis.Results: It was found that the number of the nurses with Burnout Syndrome in the hospital was 67.6%. The depersonalisation indicator in the low category was 73.5%, and the high category of self-achievement indicators had 89.2%.Conclusion: It can be concluded that improving the performance of care services is more effective through improving the quality of nursing work life. This study found that the nurses’ quality of life affected the increased nursing work service because their working scope involves interacting with other professions and the environment.